PENGARUH KEPEMIMPINAN DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PADA BANK DANAMON SIMPAN PINJAM UNIT Ps. KOTA DURI - Syafrina, Nova (Eko dan Bisnis: Riau Economic and Business Review, 2016)
The purpose of this study is to determine how much influence the leadership and competence on the performance of employees at Bank Danamon Savings and Loans Unit Ps. Duri city. The population in this study are employees of Bank Danamon Savings and Loans Unit Ps. Duri city which amounted to 32 people. Sampling was done using census techniques. The data analysis is done by using a reliability test, classic assumption test, F test, multiple regression R2 test and t test. The tests are conducted in order to determine the effect of independent variables (independend variable) with the dependent variable (dependent variable). Based on the research that the quality of service simultaneously influence the patient's satisfaction with the value of the correlation R = 0.956 which indicates a very close relationship between the leadership and competence simultaneously with the performance of employees at Bank Danamon Savings and Loans Unit Ps. Duri city. While the percentage of leadership and competence influence on the performance of employees at Bank Danamon Savings and Loans Ps. Duri city there can be adjusted R square at 0.908, which means the leadership and competence have contributed a contribution of 90.8% to the performance of employees at Bank Danamon Savings and Loans Unit Ps. Duri city, as well as the negative effect of leadership and competence positive and significant impact on patients' satisfaction with the level of leadership and 00.001 sig sig. 0,000 for competence. The conclusion that the hypothesis simultaneously and partially between the leadership and competence variables on employee performance is proven and can be accepted as true